The Main Cardiovascular Complications and Mortality Rates During the First One and a Half Years after Acute Myocardial Infarction: Data from the Prospective Outpatient Registry PROFILE-IM - S. Yu. Martsevich; N. P. Kutishenko; D. P. Sichinava; E. P. Kalaydzhyan; E. A. Kasparova; A. V. Zagrebelnyy; Yu. V. Lukina; V. A. Evdakov (Рациональная фармакотерапия в кардиологии)
Aim. To study the long-term outcomes of patients who survived after acute myocardial infarction (AMI) in a prospective outpatient registry.Material and methods. Patients (n=160) who applied to one of the outpatient clinics in Moscow after AMI were included in the registry PROFILE-MI. The total follow-up period was 1.5 years. The primary combined endpoint (PCE) included death from any cause, cardiovascular events (nonfatal myocardial infarction, nonfatal cerebral stroke), emergency hospitalizations for cardiovascular diseases, significant cardiac arrhythmias. 1-year observation period was taken in analysis of the factors affecting the development of PCE.Results. During the observation period, 16 patients (10%) died. Life status was not obtained in 4 patients. Most of the deaths were due to cardiovascular complications; in a quarter of patients, repeated AMI was the cause of death. After 12 months of follow-up, the development of PCE was observed in 42 patients. PCE has been identified more often in elderly patients, in patients who had certain complications in the acute period of AMI, in patients who had swelling at the time of the examination in the outpatient clinic, who complained of shortness of breath, and also had a heart rate (HR) more than 70 min-1. Normal blood pressure (within 120/80-139/89 mm Hg) and HR at 60-70 min-1 had a positive prognostic influence. Conclusion. Despite intensive treatment in a hospital and the relatively high quality of secondary pharmacological prevention, the prognosis of life and disease in patients after AMI remains quite serious.